Star wars. Revenge of the Sith [videorecording (Blu-Ray)] - Lucas, George, 1944-; Christensen, Hayden, 1981-; McGregor, Ewan, 1971-; Portman, Natalie, 1981-; McDiarmid, Ian (Lucasfilm Ltd, 2019)
Years after the onset of the Clone Wars, the Sith unveil a thousand-year-old plot, the Republic crumbles and from its ashes rises the evil Galactic Empire. Confirming the worst fears of Jedi Mace Windu, Anakin Skywalker is seduced by the dark side of the Force and becomes the Emperor's new apprentice-Darth Vader. The Jedi are decimated, as Obi-Wan Kenobi and Jedi Master Yoda are forced into hiding. The only hope for the galaxy are Anakin's own children, a boy and girl who share a heroic destiny.